2003
DOI: 10.1016/s1096-7192(03)00073-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dietary therapy of long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency

Abstract: Current dietary therapy for long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) or trifunctional protein (TFP) deficiency consists of fasting avoidance, and limiting long-chain fatty acid (LCFA) intake. This study reports the relationship of dietary intake and metabolic control as measured by plasma acylcarnitine and organic acid profiles in 10 children with LCHAD or TFP deficiency followed for 1 year. Subjects consumed an average of 11% of caloric intake as dietary LCFA, 11% as MCT, 12% as protein, and 66% as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 23 publications
2
80
0
1
Order By: Relevance
“…We previously reported that the concentration of plasma hydroxyacylcarnitines is related to the dietary fat intake of children with LCHAD deficiency [7]. Dietary long-chain fat intake was positively correlated and dietary MCT intake was negatively correlated with plasma hydroxyacylcarnitine concentration in 10 patients.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…We previously reported that the concentration of plasma hydroxyacylcarnitines is related to the dietary fat intake of children with LCHAD deficiency [7]. Dietary long-chain fat intake was positively correlated and dietary MCT intake was negatively correlated with plasma hydroxyacylcarnitine concentration in 10 patients.…”
Section: Discussionmentioning
confidence: 89%
“…Plasma hydroxylated acylcarnitine metabolites are closely correlated to plasma levels of the corresponding free hydroxylated fatty acids [7,28,29]. Others have speculated that the carnitine ester may be detoxifying and the free hydroxylated acid may be toxic but no data to support or refute that speculation has been published.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diet, low in fat content and hence longchain fatty acids from normal food, is supplemented with medium-chain triglycerides (MCT fat) and thereby bypasses the enzymatic defect. Supplementation with essential fatty acids is necessary to avoid deficiency (Gillingham et al 1999;Gillingham et al 2003;Spiekerkoetter et al 2009a); however, management may vary considerably (Potter et al 2012). To inhibit lipolysis, frequent feeds are necessary.…”
mentioning
confidence: 99%